1976
DOI: 10.1097/00004032-197602000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Biological Measurements in Rodents Exposed Continuously Throughout Their Adult Life to Pulsed Electromagnetic Radiation

Abstract: second with a peak electric fi,.Id intensity of 447 kV/m, a 5-nsec rise time and 550-nsev l/e fall time. The~follo*.irjg-c.-Ib )gical parameters were measured: blood chemistry, blood and bone marrow cellular conce~ntration, chromosomal aberrations, erythrocyte prodwf..ion. 3ffectsJ on fertility and reproductive, papability and appearance of tumors and other late effects. 1kt no time before and particular~y as the rodents approached the end of their life-span did any -%f the biological measurements indicate an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…However, this condition was reversible usually within 30 minutes. Other published studies on the effects of EMP on vertebrates include SKIDMORE and BAUM'S (1974), BAUM et al's (1976) and BAUMS (1979) cellular work on rats and dogs. None of these studies found significant differences between EMP-exposed and control individuals.…”
Section: Resultsmentioning
confidence: 99%
“…However, this condition was reversible usually within 30 minutes. Other published studies on the effects of EMP on vertebrates include SKIDMORE and BAUM'S (1974), BAUM et al's (1976) and BAUMS (1979) cellular work on rats and dogs. None of these studies found significant differences between EMP-exposed and control individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies of exposure to electromagnetic pulses showed no effects on fertility or on anatomical abnormalities in progeny (rodents: Baum et al [1976]), and no effects on litter size or abnormalities in newborn pups (dogs: Baum [1979]). The results obtained from the UWB-exposed rats con®rm that male embryos/fetuses exposed to an UWB electromagnetic ®eld from days 3±18 of gestation are capable of fertile matings at sexual maturity.…”
Section: Reproductive Assessment Of Male Offspringmentioning
confidence: 93%
“…Increased and decreased lymphocyte and total leukocyte counts in EMP exposed rats were also found but less frequently than changes in platelet or erythrocyte count. When the EMP exposure was continued to 94 weeks to a total of 2.5 x 10' pulses (note: 1.86 x io« pulses by calculation), hematological changes were no longer evident [Baum et al 1976]. In addition, bone marrow ceUularity was not different between groups [Skidmore and Baum 1974].…”
Section: Studies On the Biological Effects Of Electromagnetic Pulsesmentioning
confidence: 99%
“…In addition, bone marrow ceUularity was not different between groups [Skidmore and Baum 1974]. Because of these inconsistencies among hematological and hemopoietic endpoints and the absence of effect at the end of the 94 week exposure, it was concluded that EMP effect was not hazardous to rodents [Skidmore andBaum 1974, Baum et al 1976}. In a later publication, Baum (1979] did not find any effects on hematotogfol and hemapoiesis endpoints in four male and five female beagle dogs exposed to the 447 kV/m EMP pulses for 8 hr/day, for a total 45 days and 5.8 x 10 s pulses (note: 6.48 x if/ pu]ses by calculation).…”
Section: Studies On the Biological Effects Of Electromagnetic Pulsesmentioning
confidence: 99%